Foot Massage dan Joint Mobility Exercises terhadap Nilai Ankle Brachial Index (ABI) pada Pasien DM Tipe 2 - Isni Hijriana; Miniharianti Miniharianti (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the effectiveness of foot massage and joint mobility exercises on the value of ABI in type 2 DM patients. The quantitative research used a quasi-experimental approach with pre-test and post-test designs with two intervention groups. The results showed that the Wilcoxon signed ranks test statistic on 20 respondents in the two intervention groups showed a difference after being given foot massage and joint mobility exercises intervention on the ABI value, with each p-value (p = 0.00). In conclusion, foot massage and joint mobility exercises effectively improve peripheral circulation and increase ABI values in Type 2 DM patients. Keywords: Ankle Brachial Index (ABI), Type 2 DM, Foot Massage, Joint Mobility Exercises